2022
DOI: 10.1021/jacs.2c07290
|View full text |Cite
|
Sign up to set email alerts
|

Coordination-Induced Trigger for Activity: N-Heterocyclic Carbene-Decorated Ceria Catalysts Incorporating Cr and Rh with Activity Induction by Surface Adsorption Site Control

Abstract: A coordination-induced trigger for catalytic activity is proposed on an N-heterocyclic carbene (NHC)-decorated ceria catalyst incorporating Cr and Rh (ICy-r-Cr0.19Rh0.06CeO z ). ICy-r-Cr0.19Rh0.06CeO z was prepared by grafting 1,3-dicyclohexylimidazol-2-ylidene (ICy) onto H2-reduced Cr0.19Rh0.06CeO z (r-Cr0.19Rh0.06CeO z ) surfaces, which went on to exhibit substantial catalytic activity for the 1,4-arylation of cyclohexenone with phenylboronic acid, whereas r-Cr0.19Rh0.06CeO z without ICy was inactive. FT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…13 We reported that Cr-and Rh-incorporated ceria, Cr 0.19 Rh 0.06 CeO z , showed superior redox performance at low temperatures (o373 K) compared with pure ceria. [14][15][16] Cr 0.19 Rh 0.06 CeO z exhibited the redox performance of all three metal species and had remarkable NO reduction performance toward N 2 because Rh activated the CO and NO species and Cr cleaved NO species. 14,15 Thus, incorporating multiple metal species into ceria surface leads to efficient oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…13 We reported that Cr-and Rh-incorporated ceria, Cr 0.19 Rh 0.06 CeO z , showed superior redox performance at low temperatures (o373 K) compared with pure ceria. [14][15][16] Cr 0.19 Rh 0.06 CeO z exhibited the redox performance of all three metal species and had remarkable NO reduction performance toward N 2 because Rh activated the CO and NO species and Cr cleaved NO species. 14,15 Thus, incorporating multiple metal species into ceria surface leads to efficient oxidation catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular corks can also affect the structure and reactivity of catalytic metal surfaces. ,,, Recently, the use of CO on Pd/Au(111) SAAs to modify the active sites of SAA catalysts has been demonstrated via density function theory (DFT) calculations and then confirmed via experiment . DFT studies have shown the ability of CO to influence the morphology of 15 distinct SAAs .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel to these fundamental studies in surface science, NHCs have been introduced on both colloids and supported nanoparticles (NPs) to modulate their catalytic performances. ,, In these reports, the binding of NHC ligands on the metal surface is proposed to adopt a vertical monocoordinated NHC configuration. , Detailed nuclear magnetic resonance (NMR) spectroscopic investigations of silica-supported Cu species have shown that the spectroscopic signatures could in principle help to distinguish various surface sites, in particular, NHC adsorbed on isolated metal surface sites vs metallic surface sites from protonated imidazolium species (Figure b) . Nonetheless, bis-NHC metal cationic surface sites have so far not been considered on coinage metal supported on oxide surfaces, raising questions about their existence and specific (NMR) spectroscopic signatures.…”
mentioning
confidence: 99%